"The Contribution of Jiudo to Education" by Jigoro Kano. Introduction, Translation and Notes - Carlos Gutiérrez García; Mikel Pérez Gutiérrez (Universidad de León, 2012)
This paper translates and comments Jigoro Kano's (1860-1938) conference The Contribution of Judo to Education, which the founder of Kodokan Judo gave at the University of Southern California (Los Angeles) in 1932. Through its lecture not only we appreciate Kano's conception on judo, but also some of his personality characteristics revealing the amplitude of his knowledge and a humanistic character based on rationality and cooperation between individuals and countries.